Efektivitas Bibliokonseling Melalui Komik untuk Pengenalan Karier Siswa - Eva Kartika Wulan Sari; Devi Permatasari (Universitas Kanjuruhan Malang, 2022)
This research is an experimental study with a pretest posttest design, namely applying bibiliocounseling in the form of comics for the treatment given to research subjects. The research subjects were students of class VIII SMP through the selection of purposive sampling technique by taking 2 students from 5 classes who lacked career recognition. This research consists of problem identification, goal setting, counselee identification, bibliocounseling analysis, writing the initial draft of bibliocounseling material, peer evaluation, expert evaluation, development, experimentation, and evaluation. However, the researchers discussed more about the experimental results. The evaluation used is the evaluation of workmanship and evaluation of results. The data obtained in this study were reviewed with Wilcoxon, then continued with the discussion obtained from the results of evaluation and observation during experimental research. The results of the pretest showed an average score in the low to average category, this indicates that the bibliocounseling technique in the form of comics has succeeded in improving students' career recognition skills, which can be seen from the comparison of pre and post test scores. score. This means that bibliocounseling in the form of comics can improve the ability to recognize careers, which are in accordance with the abilities and desires of the ten research subjects. The suggestion given by the researcher is that the use of bibliocounseling is improved because this method is very popular with students, especially in the form of comics that can reveal to understand careers and methods of choosing a career that suits the students themselves. For researchers who want to conduct bibliocounseling research, it is better to adjust the variety of bibliocounseling that will be used, according to the characteristics of students who are research subjects.